Infantile Hypertrophic Pyloric Stenosis Following Repair of H-type Tracheoesophageal Fistula Repair and Post-operative Erythromycin Therapy - Natasha Merali; Allison R. Wilcox; Daniel P. Croitoru; Reto M. Baertschiger (EL-Med-Pub, 2019)
We present a rare case of a newborn with H-type tracheoesophageal fistula (TEF) who developed pyloric stenosis postoperatively, 10 days after he was started on erythromycin to promote gastric emptying. We report this case to describe the relationship between H-type TEF repair, erythromycin therapy, and the development of infantile hypertrophic pyloric stenosis.